AB0779 Eosinophilic myositis and rheumatoid arthritis as first manifestation in a patient carrying myotonic dystrophy type 2 (CCTG)n expenssion of ZNF9 gene. (23rd January 2014) - Meyer, A.; Theulin, A.; Chatelus, E.; Sordet, C.; Javier, R.-M.; Lannes, B.; Echaniz, A.; Geny, B.; Gottenberg, J.-E.; Sibilia, J.
Abstract : Background: Eosinophilia myopathies (EM) are a heterogeneous group of disease characterized by eosinophlic infiltration muscles associated with peripheral blood and/or bone marrow hypereosinophilia. The diagnosis of idiopathic EM is usually retained after the exclusion of accepted EM aetiologies. Recently, mutations in the CAPN3 and SGCG genes, encoding calapain-3 and γ-sarcoglycan proteins, were identified in some patients with idiopathic EM. Objectives: We report the first case of a patient with idiopathic EM and rheumatoid arthritis (RA) who carried CCTG expansion in intron 1 of the ZNF9 gene, a mutation characteristic of myotonic dystrophy type 2 (DM2). Results: A 40 years old woman presented with arthromyalgia for 4 months. She had a 18 months history of hypereosinophilia. Physical examination showed a symmetrical oedematous polyarthritis. Proximal muscles were painful but there was no muscle weakness. Eosinophilic polynuclear count was 8, 210/mm 3 . CRP amount was 11mg/L. Serum creatine kinase level was 406 IU/L. Serum tested positive for anti-citrullinated protein antibodiesand rheumatoid factor. There was no anti nuclear antibody nor ANCA. Fecal examination didn't found any parasite. Serological tests for T spiralis, T canis, A lubricoides, E histolytica, A fumigatus, E granulosus, and VIH were negative. Osteomedular biopsy showed hypereosinophilc infiltration (30%). Karyotype on myelogram was normal. Molecular analysis didn't detected Philadelphia chromosome, mutation in JAK2, KIT, PDGFRs genes nor clonal TCR rearrangement. Foots and hands radiographs, tomography of chest abdomen and pelvis, electrocardiogram and cardiac echography found no abnormality. Electromyography showed myogenic features. Muscle biopsy is presented on figure n°1. The diagnosis of idiopathic ME associated with RA was retained. The patient was successfully treated with non steroidal anti inflammatory drugs and methotrexate Ten years after, a patient's sister was diagnosed with DM2. Quadruplet repeat primed-PCR performed on the patient's blood sample found CCTG expansion in intron 1 of the ZNF9 gene. Expansion size measured with southern blot was 8 kb. At this time, there was no muscular symptom but a diabetes had appeared. Conclusions: DM2 is typically characterized by muscle weakness, myotonia, cataract and diabetes but increasingly, incomplete or atypical phenotypes are encountered. A strong incidence of autoimmune diseases, including RA, was reported in DM2 patients. In this observation, EM symptoms disappeared with immunomodulatory therapy, that argue for an authentic immunologic driven process. One explanation might be that, contrary to calpainopathies and sarcoglycanopathies, genetic lesion in DM2 does not eliminate an essential muscle protein. Instead, it induces a defect of RNA processing that may impact many different pathways including inflammation. EM with RA might be inaugural manifestations of DM2. Disclosure of Interest: None Declared